Rapid scalable fabrication of roll-to-roll slot-die coated flexible perovskite solar cells using intense pulse light annealing. Issue 23 (26th October 2022) - Chandrasekhar, P. S.; Chapagain, Sashil; Blake, Martin; Armstrong, Peter J.; Grapperhaus, Craig; Druffel, Thad L.
Abstract : Schematic illustration of custom-built roll-to-roll machine setup showing the continuous processing between the unwind and rewind stations including CDT surface preparation, deposition by slot die, drying by an air knife and thermal processing using IPL. Abstract : Perovskite solar cells have achieved high efficiencies at the lab scale using batch processes that often may not be scalable. Processes that can be integrated into a continuous manufacturing platform, such as roll-to-roll, where several processes can be carried out sequentially are necessary to develop a new cost-competitive solar technology. In this work, intense pulsed light thermal post-processing is coupled with scalable slot-die coating and air knife evaporation in a high-speed roll-to-roll process of up to 2 m min −1 . The optimization of IPL energy parameters, web speeds, solution flow rates, and concentration of precursor inks yielded a champion power conversion efficiency of 11.24% for a 1 cm 2 roll-to-roll coated device. The overall processing time for a single layer in this process is reduced from minutes to seconds and the overall footprint of the manufacturing process is decreased. This demonstrates the promising capabilities for intensed pulsed light to reduce manufacturing costs and paves a roadmap for scalable and efficient PSCs on a roll-to-roll platform.